Drug-targetting of duplex and quadruplex DNA - Gavathiotis, Evripidis (2002)
This thesis investigates structural and dynamic properties of drug recognition mechanisms to duplex and quadruplex DNA using primarily high field NMR techniques and molecular dynamics simulations. The mechanism of co-operative binding of Hoechst 33258 to the DNA minor groove of duplexes that contain two binding sites such as d(CTTTTGCAAAAG)2, d(GAAAAGCTTTC)2 and d(CTTTTGGCCAAAAG)2 has been studied. NMR and other titration techniques have evidenced co-operative binding and no detection of an intermediate 1:1 complex. High-resolution NMR structure determination showed no evidence of direct contact between Hoechst 33258 molecules or DNA structure deformation that would facilitate co-operativity, Molecular dynamics simulations based on NMR data, allowed us to calculate thermodynamic quantities of the two binding events, and lead us to conclude that ligand binding can induce changes in DNA conformational flexibility in sites of the structure distant from the binding site and result in more favourable second ligand binding. The results highlight the general importance of flexibility in determining the properties of ligand-DNA interactions. The relative importance of ligand isohelicity and phasing in DNA minor groove has been investigated by studying the structure and dynamics of the 1:1 complex of Hoechst IO-d(GCAAATTTGC)2. The results suggest that DNA sequence-dependent structure and flexibility have significant role for the strong binding of Hoechst 10 to the duplex. The formation, stability, structure and dynamics of the d(TTAGGGT)4 quadruplex structure, which contains the human telomeric repeat TTAGGG, have been studied. Characteristic features of the quadruplex structure were determined and this information was used for understanding drug-quadruplex interactions. The complex of the fluorinated polycyclic methylacridinium cation RHPS4, lead compound for telomerase inhibition, with the d(TTAGGGT)4 quadruplex structure has been investigated. RHPS4 forms a stable G-quadruplex complex by endstacking externally to the a-tetrads of the Apa and Gp'T steps. This study presents detailed properties of the complex and provides further information for lead optimisation studies.